The effect of total replacement of fish oil with DHA‐Gold® and plant oils on growth and fillet quality of rainbow trout (Oncorhynchus mykiss) fed a plant‐based diet. (10th March 2015) - Betiku, O.C.; Barrows, F.T.; Ross, C.; Sealey, W.M.
Abstract: This study investigated the effect of the replacement of fish oil (FO) with DHA‐Gold (DHA‐G)‐supplemented plant oils (PO) in rainbow trout fed plant‐protein‐based diets. Five diets (450 mg g −1 digestible protein and 150 mg g −1 crude lipid) were fed to rainbow trout (initial weight 37 ± 0.5 g) for 12 weeks in a 15 °C recirculating water system. The lipid inclusion types and levels were FO, PO and PO with DHA‐G supplemented at 30 mg g −1, 60 mg g −1 or 90 mg g −1 of the diet replacement for corn oil. Fish fed 90 mg g −1 DHA‐G were significantly larger and consumed more feed than fish‐fed PO or FO (218 g and 2.6% bwd −1 versus 181 g and 2.4% and 190 g and 2.3%, respectively). Feed conversion ratio was significantly increased in fish fed 90 mg g −1 DHA‐G (0.99) as compared to fish‐fed FO (0.90) and 30 mg g −1 DHA‐G (0.91). Panellists found trout fillets from fish fed the 90 mg g −1 DHA‐G diet to have significantly fishier aroma and flavour than fish fed the FO diet. Fatty acid analysis demonstrated that 60 mg g −1 or 90 mg g −1 DHA‐G supplementation increased PO fed fish fillet DHA to fatty acid levels equivalent or higher than those fish fed a FO diet.